2009
DOI: 10.1093/cvr/cvp388
|View full text |Cite
|
Sign up to set email alerts
|

High glucose promotes intracellular lipid accumulation in vascular smooth muscle cells by impairing cholesterol influx and efflux balance

Abstract: These results suggested that hyperglycaemia-induced foam cell formation in VSMCs was related to the imbalanced lipid flux by increasing CD36-mediated modified low-density lipoprotein uptake and reducing ABCG1-regulated cellular cholesterol efflux. Moreover, this effect was associated with increased oxidative stress and activated NF-kappaB pathway signalling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
38
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 66 publications
(42 citation statements)
references
References 37 publications
4
38
0
Order By: Relevance
“…In the last decade, several studies have shown that in addition to macrophages, VSMCs accumulate excess intracellular cholesteryl (25,26) and give rise to a significant number of foam cells in atherosclerotic lesions (14,27). Moreover, VSMC-derived foam cells in vitro lose the expression of VSMC contractile markers, transform into macrophage-like cells (15) and express monocyte chemoattractant protein-1 (MCP-1) (16,28).…”
Section: Discussionmentioning
confidence: 99%
“…In the last decade, several studies have shown that in addition to macrophages, VSMCs accumulate excess intracellular cholesteryl (25,26) and give rise to a significant number of foam cells in atherosclerotic lesions (14,27). Moreover, VSMC-derived foam cells in vitro lose the expression of VSMC contractile markers, transform into macrophage-like cells (15) and express monocyte chemoattractant protein-1 (MCP-1) (16,28).…”
Section: Discussionmentioning
confidence: 99%
“…These studies, while showing a critical role for platelet CD36 in thrombosis, do not rule out a role for CD36-mediated signaling in other vascular cells in promoting thrombosis. Although CD36 is not expressed on large-vessel endothelial cells (5,6), several groups have reported that VSMCs in culture express low levels of CD36 (7)(8)(9)(10)(11)(12) and that expression can be upregulated by PPARγ (9). No function for CD36 has been identified, however, on VSMCs.…”
Section: Introductionmentioning
confidence: 99%
“…PPAR-γ is an anti-inflammatory transcriptional factor [11]. As shown in figure 2a, we found that PPAR-γ activity was significantly decreased in the DES group (p = 0.007; fig.…”
Section: Resultsmentioning
confidence: 69%